Nanocellulose-based composites: Advancing sustainable energy storage applications - Samylingam, Lingenthiran; Aslfattahi, Navid; Kok, Chee Kuang; Kadirgama, Kumaran; Norazlianie, Sazali; Kiai, Maryam Sadat; Mohd Fairusham, Ghazali (Semarak Ilmu Publishing, 2026)
Nanocellulose, derived from renewable biomass, has emerged as a highly versatile material in sustainable energy storage. Its unique structural properties, including high surface area, mechanical strength, and tunable surface chemistry, make it an ideal candidate for integration into energy storage devices such as batteries, supercapacitors, and fuel cells. This review provides a comprehensive overview of the recent advancements in nanocellulose-based composites for energy storage applications, highlighting their role in improving electrochemical performance, enhancing mechanical stability, and promoting environmental sustainability. The discussion covers the synthesis techniques, structural modifications, and hybridization strategies used to optimize nanocellulose for energy storage, as well as the challenges associated with scalability and commercial viability. Additionally, we examine the environmental benefits of using nanocellulose composites in energy storage systems, emphasizing their potential to reduce the reliance on non-renewable materials and lower the overall carbon footprint. This review aims to provide insights into future research and development directions in this rapidly evolving field, positioning nanocellulose-based composites as a key enabler of next-generation sustainable energy technologies.